Data-driven precision marketing strategy and its effect measurement - Hong, Shengyang (Transactions on Economics, Business and Management Research, 2024)
In today’s rapidly developing digital age, data-driven precision marketing strategies have become a powerful tool for enterprises to stand out and gain key competitive advantages in fierce market competition. The beginning of this article elaborates in detail on the significant importance of data-driven precision marketing. In the current era of information explosion, through comprehensive collection, in-depth analysis, and deep mining of massive data, enterprises can gain a comprehensive and multi-dimensional understanding of consumers’ specific needs, behavior patterns, and unique preferences. Subsequently, a series of specific precision marketing strategies were discussed in depth, including important strategies such as personalized recommendations, targeted advertising, and customer segmentation. The application of these strategies can greatly improve the targeting and effectiveness of marketing activities, and effectively enhance customer satisfaction and loyalty. At the same time, the article systematically introduces the measurement methods of precision marketing effectiveness, such as the scientific application of key indicators such as conversion rate and customer lifecycle value. Finally, the crucial importance of data security and privacy protection in precision marketing was emphasized. Only by ensuring that businesses conduct marketing activities in a legal and compliant manner can they achieve the grand goal of sustainable development.